Fecundity and sexual maturity of the coral Siderastrea siderea at high latitude along the Florida Reef Tract, USA. Issue 1 (3rd March 2016) - St. Gelais, Adam T.; Chaves‐Fonnegra, Andia; Brownlee, Allison S.; Kosmynin, Vladimir N.; Moulding, Alison L.; Gilliam, David S.
Abstract: Siderastrea siderea is one of the most abundant corals at high latitude shallow sites along the Florida Reef Tract (25°–27°N). This species is able to tolerate wide seawater temperature fluctuations and sedimentation stress, but its reproductive status at high latitudes and under marginal environmental conditions is poorly understood. The objectives of this study were to evaluate the reproductive potential of S. siderea along a latitudinal gradient (25°–27°N) and to determine if sexual maturity occurs in small (<12.0 cm) S. siderea colonies. Samples of coral tissue were collected in 2007, 2008, and 2009 at three sites along the latitudinal gradient and were processed for histological analysis. Oocyte size, volume, and abundance were used to calculate fecundity. Results showed that fecundity decreased with increasing latitude and that oocyte volume was the major contributing factor to this variation. Mature oocytes were observed in S. siderea colonies at sizes as small as 1.1 cm in diameter. The ability of S. siderea to reach fertility at high latitude areas suggests this species is able to reproduce under marginal environmental conditions; however, reduction in oocyte size could increase local retention of larvae. The presence of mature oocytes in small colonies suggests that stress can reduce somatic growth and shift sexual maturity to smaller colony sizes.